The Relationship between Consumption Behavior, Income, Food Expenditure and Household Food Security in Caringin District, Bogor Regency - Herdiansyah, Dadang; Noorlatifah, Noorlatifah; Romdhona, Nur; Yunianto, Andi Eka; Asyifa, Mega; Fadly, Dzul (Universitas Airlangga, 2024)
Hunger is a condition of food insecurity. One of the efforts that can be made to reduce the incidence of food insecurity is to maintain food security, especially in households. This is an analytic observational study with a cross-sectional design with a random sample of 60 households in Caringin district, Bogor regency. Assessment of household food availability was based on a food availability questionnaire consisting of several types of food groups. Income and expenditure were measured by assessing household income. The condition of household food diversity was measured using the HDDS questionnaire. The chi-square test was used to analyze the relationship between consumption behavior, income, household expenditure, and household food security. There was a relationship between income (p=0.00) and expenditure (p=0.00) with household food security, while consumption behavior is not (p=0.14). It is concluded that there was a relationship between income and expenditure on food security, but behavior did not show an insignificant relationship. There needs to be an in-depth analysis to find other factors influencing food security apart from the variables examined in this study.